Resolução de problemas sociais com adolescentes em conflito com a lei: estratégias de mensuração e intervenção - Padovani, Ricardo da Costa (2008)
Young offenders deficits in problem solving skills are described as one of the characteristics of this population. However, there is no data in the Brazilian literature measuring this variable. This study had two aims. Firstly, a group intervention with young offenders was conducted with the aims of promoting the discrimination and emission of competent social responses associated with their psychosocial well-being (Study 1). Six male young offenders took part of the intervention program. The study was conducted in a young offenders Detention Center in the interior of São Paulo State, Brazil. Instruments used to assess the intervention were: Guided Interview, Beck Depression Inventory (BDI), Beck Anxiety Inventory (BAI), Beck Hopelessness Scale (BHS), Social Problem-Solving Inventory-Revised (SPSI-R) and, School Performance Test. The intervention program consisted of three pre-intervention sessions to gather data, and ten intervention sessions in problem-solving skills training, followed by a three month post-intervention follow-up. Results indicated a history of school failure and violence victimization, as well as the use of alcohol and drugs, and involvement in aggressive episodes. High level drop-out rates was observed in this study: only two participants were present in all phases of the intervention. In the pre-test, five participants indicated anxiety and depression, and four participants indicated hopelessness. In the post-test, one participant indicated a decrease of depression, anxiety and hopelessness; the other participant maintained of depression levels (in the low range), anxiety (low) and hopelessness (low). Five participants took part of the Follow- Up. All participants indicated a decrease of depression in that phase. In terms of anxiety, in the participants who were present in all phases, one decreased his level (from severe to low), and the other presented the same performance (low). Other participants indicated: maintenance (low and moderate) or an increase (low to moderate). In terms of hopelessness, among the participants who were present in all phases, the same performance was maintained (absence). The others showed: maintenance (moderate/low) and a decrease (severe/moderate) of performance. The Social Problem- Solving Inventory-Revised data showed that four participants performance were in the average range of the normal group, and two had deficits in this area. In post-test, one participant increased his performance, and the other maintained it. In the Follow-Up, the performance varied from average to much above average. In spite of the study s methodological limitations, this is the first study in Brazil to investigate group social problem solving skills with young offenders in a Detention Center, and the first to utilize one specific instrument to analyze social problem repertory solving in this population. The second study adapted to Portuguese the Social Problem-Solving Inventory-Revised (SPSI-R), and investigated its evidence of criteria and content validity. Seventy six male adolescents took part of study, being 38 offenders and 38 no-offenders. The study was conducted in a Young Offenders Center, and at a public school in the city of São Carlos en São Paulo State. The instrument used to assess the study was the Social Problem- Solving Inventory-Revised (SPSI-R). The instrument was applied in group, and the time of application was approximately 30 minutes. In terms of content validity, the study showed a 95% agreement among assessors. In terms of criteria validity, the results showed that the instrument could discriminate offenders from the non-offender population. The development of intervention programs and instruments specific to this population is much needed, as the numbers of studies in this area is reduced in Brazil.